Chemical Biology of Autophagy-Related Proteins With Posttranslational Modifications: From Chemical Synthesis to Biological Applications - Luo, Yu; Jiang, Chen; Yu, Lihua; Yang, Aimin (Frontiers in Chemistry, 2020)
Macroautophagy (hereafter referred to as autophagy) is an evolutionarily conserved lysosomal degradation pathway in all eukaryotic cells, which is critical for maintaining cell homeostasis. A series of autophagy-related (ATG) proteins are involved in the regulation of autophagy. The activities of ATG proteins are mainly modulated by posttranslational modifications (PTMs), such as phosphorylation, lipidation, acetylation, ubiquitination and sumoylation. To tackle molecular mechanisms of autophagy, more and more researches are focusing on the roles of PTMs in regulation of the activity of ATG proteins and autophagy process. The protein ligation techniques have emerged as powerful tools for the chemical engineering of proteins with PTMs, and provided effective methods to elucidate the molecular mechanism and physiological significance of PTMs. Recently, several ATG proteins with PTM were prepared by protein ligation techniques such as native chemical ligation (NCL), expressed protein ligation (EPL), peptide hydrazide-based NCL and Sortase A-mediated ligation (SML). More importantly, the synthesized ATG proteins are successfully used to probe the mechanism of autophagy. In this review, we summarize protein ligation techniques for the preparation of ATG proteins with PTMs. In addition, we highlight the biological applications of synthetic ATG proteins to probe the autophagy mechanism.